An empirical study on the contractual risk allocation and indemnity and hold harmless clauses in the oilfield service contracts in Malaysia - Wan Zahari, Wan Mohd Zulhafiz (Unique Conferences Canada, 2015)
Oil and gas projects are risky undertakings, which may cause severe damage to property and the environment, not to mention, personal injury and death to personnel. Contractual provision such as an indemnity and mutual hold harmless clause is used as a tool in allocating the risks. Most oil companies, in their task to manage the risks, seek to depart from the traditional form of risk allocation e.g. knock-for-knock indemnity regime. In this respect, there is a tendency that the oil companies will pass a greater share of the risks on to contractors. This problem could lead to financial impairment and unfairness to the contractors. An empirical study was conducted to investigate the issues and problems with regard to risk allocation provisions and indemnity and hold harmless clauses of oilfield service contracts in Malaysia. The data for the empirical study was drawn from the intensive semi-structured interviews of ten respondents from oil companies, contractors and one legal practitioner. The finding of this empirical study indicates that contractors are concerned about the one-way adversarial style of operator-contractor relationship and also that they are being allocated more contractual risks. The methodology employed in this paper will essentially be a combination of literature review and semi-structured interview, which will be carried out in a prescriptive and analytic manner.